Direct observation of spin-resolved valence band electronic states from a buried magnetic layer with hard X-ray photoemission. Issue 1 (31st December 2021) - Ueda, Shigenori; Sakuraba, Yuya
ABSTRACT: We report spin-resolved hard X-ray photoelectron spectroscopy (spin-HAXPES) for a buried Fe thin film in the valence band region. For the spin-HAXPES experiments, we developed an ultracompact built-in Mott-type spin-filter in a sample carrier, which enabled us to use the merit of two-dimensional (2D) multi-channel detector in a recent photoelectron analyser without modifying an apparatus for HAXPES. The effective Sherman function and the single-channel figure of merit (FOM) of the spin-filter were assessed to be −0.07 and 2.0 × 10 −4, respectively. By utilizing the 2D detector of the photoelectron analyser, the effective FOM increased by a factor of 4 × 10 4 compared to the case when only 1 channel of the 2D detector was used. We have applied spin-HAXPES to MgO(2 nm)/Fe(50 nm)/MgO(001) structures. The spin-HAXPES experiments revealed the majority and minority spin electronic states and the spin polarisation of the buried Fe thin film. Due to the large photoionization cross-section of the 4 s orbital of Fe in HAXPES, the spin-resolved spectra mainly reflected the Fe 3 d and 4 s states. The observed spin-HAXPES and spin polarisation spectral shapes agreed well with the calculated spin-resolved cross-section weighted densities of states and spin polarisation spectra. In contrast, a small discrepancy in the energy scale was recognised due to the electron correlation effects. These results suggest that the electron correlation effects are important in the electronic structure of bulk Fe, and spin-HAXPES is useful for detecting genuine spin-resolved valence band electronic structures of buried magnetic materials. Graphical abstract: uf0001